Desempenho térmico em edifícios de escritório na região central do Rio Grande do Sul - Ferreira, Francéli (2007)
This study seeks to detect the thermal performance in Office buildings as they add to a significant quantity of energy consumption in this country. Researches have revealed that 40 % of the final electricity consumption in office buildings is linked to the climate conditioning systems. Within this context there is no existence of projecting rules which establish minimum standards of thermal-electric performance in comparison to regional climatic conditions, considering the thermal variation experienced throughout the year. Thus, the present study aims to diagnose and compare the current condition of thermal performance in different types of office buildings located in six towns belonging to the central region of Rio Grande do Sul, which are included in bioclimatic zone two of Brasil. For such analysis a list of existing office buildings with at least five floors was made, in the towns of Cruz Alta, Ijuí, Lajeado, Santa Cruz do Sul, Santa Maria and Venâncio Aires. A sample of 36 buildings was selected. Following, the architecture designs and the construction information were analyzed, the buildings were sorted in five categories, according to criteria of floors number, width/depth relation of building and opaque/transparent closing area relation. For each category a representative building was selected, to which a better detail process of the construction system was made as well as internal and external temperature data for a period of thirteen days in summer and winter were recorded. The thermal performance of the buildings was assessed according to their capacity of absorption of the external thermal wave, related to its thermal inertia, opening areas and use standards of internal rooms. There was a great influence of solar radiation on the results, increased mainly by the influence on the thermal behavior of the orientation buildings of the monitored rooms, the opening area, the kind of glass and the color of opaque closings. It was noticed the necessity, for the climate of the studied region, of solar radiation control systems, so that the project decisions for the benefit of thermal conditions in summer do not cause loss in wintertime or vice-versa.